2014
DOI: 10.1165/rcmb.2013-0360oc
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Anti-G and Anti-F Antibodies on Airway Function after Respiratory Syncytial Virus Infection

Abstract: Respiratory syncytial virus (RSV) is the leading cause of lower respiratory tract illnesses in infants worldwide. Both RSV-G and RSV-F glycoproteins play pathogenic roles during infection with RSV. The objective of this study was to compare the effects of anti-RSV-G and anti-RSV-F monoclonal antibodies (mAbs) on airway hyperresponsiveness (AHR) and inflammation after primary or secondary RSV infection in mice. In the primary infection model, mice were infected with RSV at 6 weeks of age. Anti-RSV-G or anti-RSV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 47 publications
3
32
0
Order By: Relevance
“…This was evident despite 143-6C's slightly greater effect on virus replication as indicated by pulmonary virus titer and RSV RNA levels. These findings support and extend the findings described by Han et al (Han et al, 2014). In that study, RSV-infected mice treated on 2 day pi with a humanized anti–G mAb similar to 131-2G had significantly less methacholine induced airway resistance than untreated mice at days 7-10 pi.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This was evident despite 143-6C's slightly greater effect on virus replication as indicated by pulmonary virus titer and RSV RNA levels. These findings support and extend the findings described by Han et al (Han et al, 2014). In that study, RSV-infected mice treated on 2 day pi with a humanized anti–G mAb similar to 131-2G had significantly less methacholine induced airway resistance than untreated mice at days 7-10 pi.…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, 131-2G decreased pulmonary inflammation more effectively than an anti-F mAb, 143-6C, that reacts at the same antigenic site as palivizumab and like palivizumab both neutralizes RSV and inhibits RSV fusion (Anderson et al, 1988; Boyoglu-Barnum et al, 2014; DeVincenzo et al, 2014). Han et al recently reported that a humanized mAb that reacts at the same antigenic site as 131-2G also decreases airway reactivity induced by methacholine challenge and does this much more effectively than palivizumab (Han et al, 2014). These data suggest that an anti-G mAb like 131-2G might be more effective than anti-F neutralizing antibodies in treating active RSV infection.…”
Section: Introductionmentioning
confidence: 99%
“…The TRL3D3 MAb, whose affinity is high enough to neutralize the soluble G protein, has also shown direct antiviral activity with improved potency over palivizumab in mice (38). Consistent with the ex vivo effects of MAbs against RSV F or G proteins on IFN production, treatment with palivizumab was associated with increased airway inflammation in a mouse model, whereas TRL3D3 suppressed it (49). The lack of robust, long-lasting immunity following RSV infection results in frequent reinfection.…”
Section: Pharmacologymentioning
confidence: 82%
“…In in vitro studies, the RSV G protein has been noted to stimulate AEC responses and to dampen macrophage and dendritic cell responses (38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48). In vivo in mice, RSV G protein has been associated with increased weight loss, numbers of pulmonary inflammatory cells, levels of pulmonary mucus and Th2 cytokines, airway obstruction, and enhanced respiratory disease in RSV-challenged, FI-RSVvaccinated mice (18,20,21,26,31,(48)(49)(50)(51). Studies in mice have also shown that it enhances cytotoxic T cell responses (44,52), modifies adaptive immune responses (31), and, when given intravenously, suppresses respiratory rates (22).…”
Section: Discussionmentioning
confidence: 99%